2015
DOI: 10.1371/journal.pone.0136291
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Pregnancy BMI, Gestational Weight Gain, and the Risk of Hypertensive Disorders of Pregnancy: A Cohort Study in Wuhan, China

Abstract: BackgroundHypertensive disorders of pregnancy (HDP) are major causes of maternal death worldwide and the risk factors are not fully understood. Few studies have investigated the risk factors for HDP among Chinese women. A cohort study involving 84,656 women was conducted to investigate pre-pregnancy BMI, total gestational weight gain (GWG), and GWG during early pregnancy as risk factors for HDP among Chinese women.MethodsThe study was conducted between 2011–2013 in Wuhan, China, utilizing data from the Materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 32 publications
(47 reference statements)
5
38
0
4
Order By: Relevance
“…The WMCHMIS was introduced in our previous study. 21 Enrolled women included every pregnant woman who had a live, singleton newborn from 1 January 2010 to 23 May 2016. The study has been approved by the Wuhan Children’s Hospital (Wuhan Maternal and Child Healthcare Hospital).…”
Section: Methodsmentioning
confidence: 99%
“…The WMCHMIS was introduced in our previous study. 21 Enrolled women included every pregnant woman who had a live, singleton newborn from 1 January 2010 to 23 May 2016. The study has been approved by the Wuhan Children’s Hospital (Wuhan Maternal and Child Healthcare Hospital).…”
Section: Methodsmentioning
confidence: 99%
“…Maternal size can make the assessment of fetal size, presentation and external monitoring of fetal heart tracing more challenging during pregnancy. Initiation and maintenance of breastfeeding are also more difficult in the women with obesity . High prepregnancy BMI is associated with a small but statistically significant increase in severe maternal morbidity or mortality, with the adjusted rate difference per 10 000 women compared with normal BMI being 24.9 (95% CI 15.7–34.6) for women with class I obesity, 35.8 (95% CI 23.1–49.5) for women with class II obesity and 61.1 (95% CI 44.8–78.9) for women with class III obesity .…”
Section: Introduction and Background Epidemiologymentioning
confidence: 99%
“…Initiation and maintenance of breastfeeding are also more difficult in the women with obesity. 1,[5][6][7][8][9][10][11][12][13][14][15][16][17] High prepregnancy BMI is associated with a small but statistically significant increase in severe maternal morbidity or mortality, with the adjusted rate difference per 10 000 women compared with normal BMI being 24.9 (95% CI 15.7-34.6) for women with class I obesity, 35.8 (95% CI 23.1-49.5) for women with class II obesity and 61.1 (95% CI 44.8-78.9) for women with class III obesity. 18 These US data are supported by the 2015 MBRRACE-UK (Mothers and Babies: Reducing Risk through Audits and Confidential Enquiries across the UK) review into maternal deaths, which reported that 30% of women who died were obese and 22% were overweight.…”
Section: Introduction and Background Epidemiologymentioning
confidence: 99%
“…It is suggested that the incidence of HDP has increased over time probably due to advanced maternal age and increased occurrence of obesity and diabetes in mothers (13,14). The pathophysiology of HDP is not fully elucidated but seems to involve maternal, fetal and placental factors (14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%